Metabolites changes of a low-temperature and low-salt fermented Chinese kohlrabi during fermentation based on non-targeted metabolomic analysis - Zhao, Zhiping; Chen, Hongfan; Zhang, Yulin; Nie, Xin; Xiang, Lu; Peng, Tao; Liu, Dayu; Luo, Huailiang; Wang, Aili (Frontiers in Sustainable Food Systems, 2023)
A low-temperature and low-salt industrially fermented Chinese kohlrabi (LSCK) was developed in this study, with the salt usage decreased by approximately 70% compared to the traditional high-salt fermented Chinese kohlrabi (HSCK). The differences in physicochemical properties, metabolites and overall flavors during LSCK fermented for 0, 45 and 90 days (d) were analyzed by gas chromatography−time−of−flight mass spectrometry (GC−TOF−MS), electronic nose (E−nose) and other techniques. The results showed that the total acid content increased significantly from 3.68 g/kg to 8.59 g/kg. However, the protein content significantly decreased from 2.52 g/100 g to 0.66 g/100 g. The number of lactic acid bacteria cells increased significantly from 3.69 log10CFU/g to 4.46 log10CFU/g. Based on multivariate statistical analysis, 21, 14 and 15 differential metabolites were identified in the three treatment groups A1 (0 d and 45 d), A2 (45 d and 90 d), and A3 (0 d and 90 d) respectively (VIP > 1, P < 0.05, |log2FC| ≥ 1.1). Carbohydrates, sugar alcohols, amino acids and their derivatives were the main differential metabolites in the LSCKs fermented for different periods. Aminoacyl−tRNA biosynthesis and glycine, serine and threonine metabolism pathways significantly correlated with the differential metabolites based on Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis (P < 0.05). Furthermore, the overall odors were significantly different among the LSCKs with different fermentation periods, as detected by E−nose. The present study describes the change trend of metabolites during LSCK fermentation and elucidates important metabolic pathways in LSCK, providing a theoretical basis for the target regulation of functional metabolites in kohlrabi and the optimization of LSCK processing.